1992
DOI: 10.1111/j.1600-051x.1992.tb01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin and the gingival tissues

Abstract: Cyclosporin is a selective immunosuppressant that has a variety of applications in medical practice. Like phenytoin and the calcium channel blockers, the drug is associated with gingival overgrowth. This review considers the pharmacokinetics, pharmacodynamics, uses and unwanted effects of cyclosporin, in particular the action of the drug on the gingival tissues. Clinical and cell culture studies suggest that the mechanism of gingival overgrowth is a result of an interaction between the drug and its metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
35

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(153 citation statements)
references
References 79 publications
3
115
0
35
Order By: Relevance
“…O sucesso do seu uso sistemático trouxe como conseqüência natural a extensão da indicação terapêutica para algumas das manifestações de doenças auto-imunes 3,4,5 . Entre os efeitos adversos desta medicação, alguns autores observaram o aumento do volume gengival 6,7,8 .…”
Section: Introductionunclassified
“…O sucesso do seu uso sistemático trouxe como conseqüência natural a extensão da indicação terapêutica para algumas das manifestações de doenças auto-imunes 3,4,5 . Entre os efeitos adversos desta medicação, alguns autores observaram o aumento do volume gengival 6,7,8 .…”
Section: Introductionunclassified
“…Previous immunosuppressive regimens used oral dosages of 10 to 20 mg/kg/d during the organ maintenance phase. 5 The mean CsA dosage in this study was 3.2 mg/kg/d (or 220 mg/d). This value is consistent with that reported in some previous studies, 8,16 but less than the median values reported in Thomason et al's 15 study (350 mg/d for CsA + CCB group, and 300 mg/day for CsA group).…”
Section: Discussionmentioning
confidence: 99%
“…4 The prevalence of GO ranges from 25% to 81%, depending on the study population, index, doses, serum levels, treatment duration, and interactions with concurrently administered drugs. 5,6 Mechanisms proposed to explain the occurrence and distribution of GO point to a multifactorial model. Other factors seem to be associated with GO and cyclosporine therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Lack of good plaque control and the presence of gingivitis, independently from the drugs used, aggravate the drug-induced gingival enlargements. 11,47,48 Most of the evidence about the relationship between bacterial plaque and gingival enlargement was obtained from cross-sectional studies. It is not clear exactly whether plaque is an aggravating factor of gingival enlargement or forms as a result of morphological changes in the gingiva.…”
Section: Risk Factorsmentioning
confidence: 99%